BAKU MUTU ARSEN PADA TANAH INCEPTISOL GROBOGAN DENGAN TANAMAN INDIKATOR PADI - Wahyu Purbalisa; Anik Hidayah; S Sukarjo (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Farmers use pesticides intensively in the cultivation of rice. The use of organic and inorganic fertilizers give in large quantities. Pesticides, organic and inorganic fertilizers contain heavy metals arsenic, so the provision of large amounts will accumulate in the soil. In addition to nutrients, rice plant tissue will absorb heavy metals including arsen. Indonesian government has implemented a quality standard of arsen in cerealia by 0.5 mg kg-1. This study was aimed to obtain quality standard of arsenic in an Inceptisol at planting of rice. Research conducted at the scale of pot to contaminate soil planted rice with rows 0 mg kg-1, 15 mg kg-1, 30 mg kg-1, 60 mg kg-1. Data observed that plant growth, yield and content of arsenic in the soil and plant tissue. Agronomic parameters and yield components performed statistical analysis of variance followed by Tukcey test. Growth and crop yield based on statistical analysis are significantly different. The quality standard of heavy metals on soil done by regression analysis between the content of arsen in the soil and rice seed. By incorporating quality standards of arsenic on the rice on the regression equation, obtained the quality standard of arsen in the soil. The analysis results obtained that the quality standards arsenic in an Inceptisol of Grobogan in the soil planting of rice of 17.5 mg kg-1.